Crystallization of FeOOH via iron salts: an anion-chemoaffinity controlled hydrolysis toward high performance inorganic pseudocapacitor materials1. Issue 9 (7th March 2015) - Zhang, Mu; Chen, Kunfeng; Chen, Xu; Peng, Xiaoyang; Sun, Xudong; Xue, Dongfeng
<x xml:space="preserve">Abstract</x> Low temperature hydrolysis reactions are designed to study the chemical roles of anions with different chemoaffinity abilities to iron ions on the crystallization of FeOOH.